Influence of color plastic mulch and thermal blanket in watermelon cv. 'Santa Amelia' (Citrullus lanatus Thunb.) - Solis-Rosas Diaz , Luis F. (2021)
The scope of this study was based on analyzing the productivity, quality and earliness of the watermelon crop cv. ‘Santa Amelia’ grown on the central coast using polypropylene mulch of different shades using the blanket ends in certain treatments. Eight treatments were studied, mulch white, black and transparent color only, in combination with thermal blanket, thermal blanket alone and control. Completely randomized Block Design was used. The results showed a superior production when using only mulch and mulch more thermal blanket.: Black mulch more thermal blanket with 81,37; white mulch with 75,95; transparent mulch 74,53 and black mulch 74,45 Tn*ha respectively very higher than the control with 45,27 Tn*ha. Regarding the early harvest, the treatment with black mulch in its first harvest achieved 34,75 percent, a result similar to that to which mulch was applied alone and in combination with a thermal blanket, beating the treatment with only thermal blanket with 17,38 and control with 5,1 percent respectively. Regarding the factor of the fruit length over width, being the longest fruit when the factor is higher, the mulch combined with thermal blanket obtained the first place statistically which are the black, white and transparent mulch in combination with thermal blanket with a result of 1,36; 1,34 and 1,31 respectively.